Ammonium-mediated reduction in salicylic acid content and recovery of plant growth in Arabidopsis siz1 mutants is modulated by NDR1 and NPR1. (2nd September 2021) - Kim, Ju Yong; Song, Jong Tae; Seo, Hak Soo
ABSTRACT: The siz1 mutants exhibit high SA accumulation and consequently severe dwarfism. Although siz1 mutants exhibit growth recovery upon exogenous ammonium supply, the underlying mechanism remains unknown. Here, we investigated the effect of ammonium on SA level and plant growth in SA-accumulating mutants. The growth of siz1-2 and siz1-3 mutants was recovered to wild-type (WT) levels upon exogenous ammonium supply, but that of siz1-3 ndr1 ( non-race-specific disease resistance 1 ) and siz1-3 npr1 ( non-expressor of pathogenesis related gene 1 ) double mutants was unaffected. The SA level was decreased by exogenous ammonium application in siz1-3 ndr1, siz1-3 npr1, and siz1-3 mutants. The level of nitrate reductase (NR) was almost the same in all genotypes (WT, siz1-3, ndr1, npr1, siz1-3 ndr1, and siz1-3 npr1 ), regardless of the ammonium treatment, suggesting that exogenous ammonium supply to ndr1 siz1-3 and npr1 siz1-3 double mutants does not have any effect on their growth and NR levels, but decreases the SA level. Taken together, these results indicate that ammonium acts as a signaling molecule to regulate the SA amount, and NDR1 and NPR1 play a positive role in the ammonium-mediated growth recovery of siz1 mutants.